Effectiveness Of Using Extension Method On Syntax Ability Of Children With Language Disorders In Slb C Kerten Surakarta - Wati, Ria Rahma; Putra, Sinar Perdana; Sudarman, Sudarman (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Syntactic ability is an important ability in the process of communicating in everyday life. Mastery of grammar is needed so that information can be conveyed and received well. Each child has different varieties from one another. Some children may also experience delays or even problems with their language. The results of mapping speech delay cases show that 16 Inclusive Elementary Schools with state status in Surakarta City have students with special needs who experience speech delay problems. Language disorders have many characteristics, including the inability to form sentences (syntax). Based on this, the researcher wants to know how effective extension methods are on the syntactic abilities of children with language disorders. The method one group pre-test and post-test design used a purposive sampling technique. The mean syntactic proficiency rose from 39.35% before therapy to 54.88% after treatment. The syntax proficiency of children improved by 15.53%. Conclusion The extension method effectively improves children's syntax with language disorders in SLB C Kerten Surakarta.